Havana preserve us! Food preservation techniques on Cuban radio - Figueroa, Vilda (Technical Centre for Agricultural and Rural Cooperation, 2006)
Havana is a Mecca for urban agriculture, but a scarcity of refrigeration results in considerable wastage. One project is using that venerable old ICT - radio to get out the food preservation message.